2019
DOI: 10.1038/s41598-019-50405-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Value of Soluble Urokinase-type Plasminogen Activator Receptor (suPAR) in Focal Segmental Glomerulosclerosis and Impact of Detection Method

Abstract: the plasma soluble urokinase-type plasminogen activator receptor (supAR) is a biomarker for focal segmental glomerulosclerosis (fSGS), but its value is under discussion because of ambiguous results arising from different ELISA methods in previous studies. The aim of this study was to compare diagnostic performance of two leading suPAR ELISA kits and examine four objectives in 146 subjects: (1) plasma suPAR levels according to glomerular disease (primary, secondary and recurrent FSGS after kidney transplantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 45 publications
2
36
1
Order By: Relevance
“…This interaction is further enhanced among African Americans who carry the highrisk APOL1 genotype [8]. This effect on the glomeruli leading to proteinuria is consistent with the recently reported greater values of suPAR among patients with focal segmental glomerulosclerosis [9].…”
Section: Positionsupporting
confidence: 89%
“…This interaction is further enhanced among African Americans who carry the highrisk APOL1 genotype [8]. This effect on the glomeruli leading to proteinuria is consistent with the recently reported greater values of suPAR among patients with focal segmental glomerulosclerosis [9].…”
Section: Positionsupporting
confidence: 89%
“…Differences in the assays used to measure suPAR may also contribute to variations in suPAR values. A recent study comparing the assay used by our hospital (suPARnostic R AUTO Flex ELISA) to another common assay (Quantikine R Human uPAR-Immunoassay) found that suPARnostic R yielded significantly lower suPAR in healthy controls and higher suPAR in patients with kidney disease (Winnicki et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
“…Since suPAR can be cleaved into several shorter molecules, some authors suggested that a hypoglycosylated fragment not readily detected by standard assays, rather than full-length suPAR, could be responsible for FSGS pathogenesis (52). In a recent study, a novel method able to identify both full-length and suPAR fragments outperformed the conventional ELISA assay in discriminating FSGS cases from other proteinuric nephropathies in a single-center cohort (53), but external validation has not been reported yet.…”
Section: Maladaptive Genetic Infectious and Toxic Risk Factorsmentioning
confidence: 99%